Performance of the anaerobic co-digestion of pig manure with the inclusion of crude glycerine - Schwingel, Alice Watte [UNESP]; Amorim Orrico, Ana Carolina; Previdelli Orrico Junior, Marco Antonio; Sunada, Natalia da Silva; Centurion, Stanley Ribeiro (Univ Federal Ceara, Dept Geol, 2016)
The aim of this study was to evaluate the performance of the anaerobic co-digestion of pig manure associated with increasing doses of crude glycerine, adopting different periods of hydraulic retention time (HRT). A completely randomised design was used in a 3 x 4 factorial scheme, three HRT (10, 17 and 24 days) and four doses of crude glycerine (0, 5, 10 and 15% of the total solids), with four replications per treatment. The parameters to be evaluated were biogas production and potential production, reduction in total solids (TS), neutral detergent fibre (NDF) and acid detergent fibre (ADF). Biogas production and potential production displayed a quadratic effect for an HRT of 17 and 24 days, showing the doses of 4.09% and 5.63% crude glycerine to be respectively optimal for production, and 4.52% and 5.42% crude glycerine for production potential. There was no difference between the doses of crude glycerine at the HRT of 10 days for reductions in TS. However, a difference was seen between doses at HRT 17 and 24, with the greatest reduction of 54.9% being found when including 5% of crude glycerine at the greatest HRT. The reductions in NDF and ADF were greater with the addition of crude glycerine for an HRT of 10 and 17 days. The inclusion of 4% - 6% crude glycerine at HRT 24 was more efficient in the production of biogas and reducing TS and NDF. With a view to a greater reduction in ADF, higher doses of glycerine can be used in the co-digestion of pig manure.
Keywords: Biodiesel; Waste; Pig farming; Hydraulic retention time